Efficacy and Safety of Vitamin D Adjuvant Therapy for Ulcerative Colitis: A Meta-Analysis. (20th July 2022) - Guo, Xinyi; Liu, Changxing; Huang, Yahui
Abstract : Objective. To examine the clinical efficacy and safety of Vitamin D in the treatment of ulcerative colitis in a systematic manner. Methods . RCT studies on Vitamin D in the treatment of ulcerative colitis were searched from CNKI, Wanfang Data, PubMed, Cochrane Library, and Web of Science databases. RevMan 5.4 software was used for analysis. Results . 10 articles were included, including 1077 patients. Meta-analysis results showed that when clinical efficacy was used as the outcome index, the clinical efficacy of the oral vitamin group was higher than that of the conventional treatment group (OR = 4.07, 95% CI 2.64-6.27), and the difference was statistically significant (Z = 6.38, P < 0.00001 ). When the Mayo risk score was used as the outcome index, the difference was statistically significant, indicating that oral Vitamin D significantly reduced the Mayo risk score (MD: -0.41, CI = − 0.47, − 0.34, Z = 13.09, P < 0.00001 ). Using the intestinal mucosal barrier as the outcome index, the results showed that (1) the MDA group (MD = − 0.75, 95% CI (-0.96 -0.53), P < 0.00001 ), (2) the DAO group (MD = − 1.17, 95% CI (-1.39-0.95), P < 0.00001 ), and the Vitamin D group could effectively improve intestinal mucosal barrier function after sensitivity analysis (MD = − 1.00, 95% CI (-1.08-0.92), P < 0.00001 ). When inflammatory factors were used as outcome indicators, IL-6, TNF- α, and CRP groups had statistical significance (MD = − 4.50, 95% CI (-5.13-3.87), P < 0.00001 ); MD = − 7.27, 95% CI (18.96-5.58), P < 0.00001 ; and MD = − 1.49, 95% CI (-1.76 -1.23), P < 0.00001, respectively). When the incidence of adverse reactions was used as the outcome indicator (OR = 0.73, 95% CI (0.34-1.32), P = 0.23 ), there was no significant difference between the two groups. Conclusion . Vitamin D combined with mesalazine is effective in the treatment of ulcerative colitis, by improving the Mayo score and intestinal barrier function, and reducing inflammatory factors, with no significant safety difference. However, due to the quality of the included researches, more RCT researches needed to provide sufficient evidence to support clinical application. This study is registered with INPLASY 202250044.